Drug resistance in respiratory infections and Lysin as a Potential Therapeutics: A review - Seeam, Tanveer Ahmed; Dey, Shajib; Sadmeen, Sanjana; Tannum, Afifa (2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.